Wellbeing in line managers during mandatory working from home: How work and personal factors combine - van Gelder, Marco; van Veldhoven, Marc; van de Voorde, Karina (Frontiers in Psychology, 2022)
The pandemic, particularly the aspect of forced working from home, has had a major impact on the workforce. Previous studies show that line-managers have also experienced severe mental strain during this period. Since it is expected that hybrid working will be more the new normal than the exception in the future, this study further examined line-managers’ work-related wellbeing in terms of engagement and exhaustion. Following the Job Characteristics Model (JCM), we explore the mediating role of meaningful work between workplace innovation before the pandemic and line-managers’ work-related wellbeing during forced working from home. The underlying idea is that organizations that already adopted workplace innovation practices before the pandemic, give teams and employees more control, thus allowing a more meaningful role for line-managers, which positively impacts line-managers' work-related wellbeing during the pandemic. In addition, building upon Job Demands-Resources Theory (JDR) and the role of personal resources therein, we explore digital leadership skills and work-life segmentation preference as moderators between meaningful work and work-related wellbeing. Our findings show that workplace innovation is positively associated with engagement via its effect on meaningful work, but not associated with exhaustion. Secondly, we found that work-life segmentation preference amplifies the relation between meaningful work and engagement (positive link) as well as exhaustion (negative link). This indicates that line-managers with a high work-life segmentation preference who have a low score on meaningful work, experience less engagement and more exhaustion than line-managers with a high score on meaningful work when working from home. No support was found for moderation of digital leadership skills in the relationship between meaningful work, engagement, and exhaustion. Based on these results we discuss implications for research, and we provide practice recommendations.